2023
DOI: 10.1590/fst.105422
|View full text |Cite
|
Sign up to set email alerts
|

Papaya seeds (Carica papaya L. var. Formosa) in different ripening stages: unexplored agro-industrial residues as potential sources of proteins, fibers and oil as well as high antioxidant capacity

Abstract: Considering the information presented above, the use of papaya seeds to obtain new products is a promising alternative, because it could add value to a by-product, provide new ingredients to the food industry, and diminish the disposal of agro-industrial wastes. Many studies have already evaluated different ways of extracting oil from papaya seeds (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Also, papaya seeds contain lower amounts of linoleic acid, allowing a reduction in oxidation potential, and consequently, a longer shelf life to several products, which is an advantage for potential industrial applications in food, pharmaceutical, and cosmetic industries. Mesquita et al [2], Yao and Xu [37], and Santana et al [38] reported similar results for papaya oil seeds obtained from several papaya varieties. According to these researchers, papaya seeds may contain 30-40% of oil, making them as economically useful by-product.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Also, papaya seeds contain lower amounts of linoleic acid, allowing a reduction in oxidation potential, and consequently, a longer shelf life to several products, which is an advantage for potential industrial applications in food, pharmaceutical, and cosmetic industries. Mesquita et al [2], Yao and Xu [37], and Santana et al [38] reported similar results for papaya oil seeds obtained from several papaya varieties. According to these researchers, papaya seeds may contain 30-40% of oil, making them as economically useful by-product.…”
Section: Discussionmentioning
confidence: 58%
“…Polyphenols have gained popularity in recent decades, owing mostly to their potential benefits to human health, resulting from their significant bioactivities (antioxidant, anti-inflammatory, antimicrobial, antidiabetic, among others) [2,11,40]. These bioactive molecules can be collected from by-products using several technologies and used to generate a variety of valorized products, such as functional foods or dietary supplements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural and food residues are the main organic waste produced worldwide, which could generate between 6 and 10% of greenhouse gas emissions (Teigiserova et al, 2020). In this context, the circular economy emerges as a strategy that seeks to mitigate the environmental impact generated by agro-industrial waste, giving it a new application in productive chains (León-Roque et al, 2023;Mesquita et al, 2023), for example, the extraction of bioactive compounds (Tirado et al, 2019).…”
Section: Introductionmentioning
confidence: 99%